Catastrophe Insurance Policy for China - Wang, Jun (World Bank, Washington, DC, 2012)
The vast majority of China's population lies to the southeast of a line running from Beijing to Sichuan. This entire region is subjected to major floods each year, while typhoons affect the southern and eastern coastal areas and major earthquakes affect the western and northern margins. The average annual direct property damage is estimated at approximately USD 15 billion, and when combined with other immediate economic losses, including business interruption, disaster relief, and other costs, is considerably larger. As with other sectors, insurance in China is growing rapidly, with a compounded annual growth rate of 25 percent since 2001. The property insurance industry, nevertheless, is underdeveloped. Total property premiums in China are about USD 15 billion, whereas the losses from the Wenchuan earthquake alone are likely to exceed USD 100 billion. According to most estimates, only 5 percent of property in China is insured, primarily among commercial and industrial users. When it comes to private dwellings, it is estimated that today only 1 out of 100 is insured against natural hazards. Clearly, the current property insurance market in China is dwarfed by the nation's need for catastrophe risk protection; at the present level of insurance penetration, China's insurance industry cannot provide significant compensation for large natural hazards losses.